Analysis of Physics Practicum Problems Faced by Students during Distance Learning - Napsawati Napsawati; Fitriani Kadir (Jurnal Pendidikan Fisika, 2022)
Practicum is an important part of science education. The purpose of this research is to examine the practical challenges encountered by students at MTs DDI Sepange during distant learning, as well as the various solutions proposed. This is a qualitative descriptive study with a sample size of 24 students. Data were gathered through observation and open interviews with sciences subject teachers and a number of students. Furthermore, researchers employed a questionnaire approach to assess the viability of problem-solving solutions. The findings revealed that the problems encountered by students during the pandemic were related to the implementation of practicum, specifically that the process of implementing the practicum was not properly carried out, the availability of tools and materials to carry out the practicum was very limited, and it was difficult to carry out the practicum without direct guidance and instructions from the teacher. Based on these problems, the solution suggested to solve practical obstacles during distance learning is practicum guidelines involving the use of simple materials and tools found in the students' surroundings.